Reinterpretasi Makna Jihad dalam Al-Qur’an dan Hadis: Upaya Kontekstualisasi di Masa Kini - Khaerul Umam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
The aim of this research is to gain knowledge about the concept of the true meaning of jihad. Using qualitative methods supported by literature review with various stages containing content analysis. With the final result stating that Jihad in Islam has a broad and deep meaning. Etymologically, jihad comes from the Arabic word